(untitled) - Hartmann, Pamela (New York,Tp. Hồ Chí Minh, 2009)
Interactions Mosaic, Silver Edition is the newly revised five-level, four-skill comprehensive ESL/EFL series designed to prepare students for academic content. The themes are integrated across proficiency levels and the levels are articulated across skill strands. The series combines communicative activities with skill-building exercises to boost students' academic success.
Keywords: English language,Reading comprehension